2017
DOI: 10.1136/bcr-2017-221638
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract aspergillosis in a patient with chronic kidney disease

Abstract: Invasive aspergillosis is a life-threatening fungal infection, especially in immunocompromised patients. Pulmonary aspergillosis is the most common type of the infection, while urinary tract infection is relatively rare. Here, we describe a case of a 46-year-old man with chronic renal disease presenting with intermittent abdominal pain. The diagnosis of aspergillosis was established by pathological findings of the fungal ball in the bladder. The patient underwent multiple antimicrobial treatments and surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…In a case report by El Saleeby et al, Aspergillus terreus was reported in a case of CKD similar to case 1 (5). Aspergillus infections of the urogenital tract are very rare (6). In case 1, A. terreus was reported in a case of CKD with scrotal swelling who is immunocompromised having diabetes.…”
Section: Design: Retrospective Case Seriesmentioning
confidence: 88%
“…In a case report by El Saleeby et al, Aspergillus terreus was reported in a case of CKD similar to case 1 (5). Aspergillus infections of the urogenital tract are very rare (6). In case 1, A. terreus was reported in a case of CKD with scrotal swelling who is immunocompromised having diabetes.…”
Section: Design: Retrospective Case Seriesmentioning
confidence: 88%
“…55 Aspergillus spp., a common airborne mold that accounts for up to 40% of fungal contamination, has also reported as a cause of UTIs. [49][50][51] Nevertheless, aspergillosis limited to the urinary tract is an uncommon invasive aspergillosis type, which most often affects the lungs. 49 Pathological renal disease caused by Aspergillus infection has as characteristic multiple micro-abscesses, which indicate a hematogenous spread to the kidney.…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…[49][50][51] Nevertheless, aspergillosis limited to the urinary tract is an uncommon invasive aspergillosis type, which most often affects the lungs. 49 Pathological renal disease caused by Aspergillus infection has as characteristic multiple micro-abscesses, which indicate a hematogenous spread to the kidney. 50 Moreover, it has been reported as a causative of the ureteric fungal ball leading to obstructive uropathy in leukemia and renal allograft patients.…”
Section: Fungal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Localized aspergillosis of the renal graft was reported in a child 5 months after kidney transplantation [61]. A case of urinary tract aspergillosis presenting as an aspergilloma of the urinary bladder has also been described [66].…”
Section: Aspergillosis Of the Genitourinary Tractmentioning
confidence: 99%